2013
DOI: 10.1186/1475-2875-12-332
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic versus cytocidal profiling of quinoline drug combinations via modified fixed-ratio isobologram analysis

Abstract: BackgroundDrug combination therapy is the frontline of malaria treatment. There is an ever-accelerating need for new, efficacious combination therapies active against drug resistant malaria. Proven drugs already in the treatment pipeline, such as the quinolines, are important components of current combination therapy and also present an attractive test bank for rapid development of new concepts.MethodsThe efficacy of several drug combinations versus chloroquine-sensitive and chloroquine-resistant strains was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 63 publications
0
36
2
1
Order By: Relevance
“…In clinical studies, artemether-LMF treatments have been found to select for wildtype pfcrt K76 (43,44), pfmdr1 N86 (43,45), and N1042 (45) alleles, as well as increased pfmdr1 copy numbers (40,46). Our finding of the PQ-CQ synergistic interaction in the CQR Dd2 strain was different from the additive effect observed earlier in the same strain (28), but similar to another observation in the CQR K1 strain (25). As speculated earlier, the inconsistent results for PQ-CQ interactions in different parasite strains may be due to other unknown factors rather than to the pfcrt mutations (28).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In clinical studies, artemether-LMF treatments have been found to select for wildtype pfcrt K76 (43,44), pfmdr1 N86 (43,45), and N1042 (45) alleles, as well as increased pfmdr1 copy numbers (40,46). Our finding of the PQ-CQ synergistic interaction in the CQR Dd2 strain was different from the additive effect observed earlier in the same strain (28), but similar to another observation in the CQR K1 strain (25). As speculated earlier, the inconsistent results for PQ-CQ interactions in different parasite strains may be due to other unknown factors rather than to the pfcrt mutations (28).…”
Section: Discussioncontrasting
confidence: 56%
“…Our finding of the PQ-CQ synergistic interaction in the CQR Dd2 strain was different from the additive effect observed earlier in the same strain (28), but similar to another observation in the CQR K1 strain (25). As speculated earlier, the inconsistent results for PQ-CQ interactions in different parasite strains may be due to other unknown factors rather than to the pfcrt mutations (28).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations